Lower expression of PH domain leucine-rich repeat protein phosphatase 1 (PHLPP1) association with poor prognosis of gastric cancer - Hou, Yachao (Int J Clin Exp Med, 2015)
Background: The aim of this study was to investigate the expression of PH domain leucine-rich repeat protein phosphatase 1 (PHLPP1) in gastric cancer (GC), and its potential influence on the prognosis of GC patients. Methods: At present study, we examined the immunohistochemical expression of PHLPP1 on tissue microarrays (TMAs) containing 135 gastric adenocarcinoma tissues and 135 matched adjacent non-tumor tissues. In addition, both semi-quantitative reverse transcription polymerase chain reaction (RT-PCR) and western blotting analysis (WB) were adopted to detect of the expression of PHLPP1 in the GC cell lines (AGS, SUN-1, KATO-III, BGC-823, MGC-803, SGC-7901, and HGC-27) and the normal gastric cell line GES-1. Survival analysis was used to investigate the efficiency of the prognostic evaluation of PHLPP1 expression in GC patients. Results: Positive expression rate of PHLPP1 in the primary GC tissues was significantly lower than that in adjacent non-tumor tissues (55.6% vs. 87.4%, P<0.001). Both gene transcription (mRNA) and Protein expression of PHLPP1 in the GC cell lines were significantly lower than those in the GES-1 cell line, respectively. The Kaplan-Meier analysis showed that patients presented PHLPP1 negative expression in the GC tissues had significantly lower overall survival rate than those presented PHLPP1 positive expression in the GC tissues (P=0.008). With the multivariate survival analysis (Cox regression), PHLPP1 expression in the GC tissue was identified as an independent predictor of the survival of patients. Conclusions: This study indicated that aberrant PHLPP1 expression was observed in GC tissues, which was significantly associated with the poor prognostic outcomes of GC patients.